Fortalecimiento del discurso oral y uso lexical en estudiantes de décimo grado de la institución Liceo Mayor de Palermo desde un enfoque pedagógico y sociolingüístico a partir de técnicas de comunicación oral (2021)
Oral expression and lexical use as a fundamental part of human development are necessary in different personal, social and academic spheres. In this sense, this research Monograph has as its main objective to strengthen oral discourse and the use lexical in 10th grade students of the Liceo Mayor de Palermo institution, making use of oral communication techniques, from a pedagogical and sociolinguistic approach.